Long‐lasting persistence of large B‐cell clones in hepatitis C virus‐cured patients with complete response of mixed cryoglobulinaemia vasculitis. (15th February 2019) - Visentini, Marcella; Del Padre, Martina; Colantuono, Stefania; Yang, Baoran; Minafò, Ylenia Aura; Antonini, Silvia; Carnovale, Myriam; De Santis, Adriano; Pulsoni, Alessandro; De Sanctis, Giuseppe Maria; Gragnani, Laura; Zignego, Anna Linda; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV)‐related mixed cryoglobulinaemia vasculitis (MCV) is characterized by the expansion of rheumatoid factor‐producing B‐cell clones. The aim of this study was to assess whether B‐cell clones may persist in these patients after the clearance of the virus with antiviral therapy, and whether their persistence influences clinical outcomes. Methods: Forty‐five HCV‐cured MCV patients were followed up for a median of 18.5 (range 9‐38) months after the clearance of HCV. Circulating B‐cell clones were detected using flow cytometry either by the skewing of kappa/lambda ratio or by the expression of a VH 1‐69‐encoded idiotype. Results: The clinical response of vasculitis was 78% complete, 18% partial and 4% null. However, cryoglobulins remained detectable in 42% of patients for more than 12 months. Circulating B‐cell clones were detected in 18 of 45 patients, and in 17 of them persisted through the follow‐up; nine of the latter patients cleared cryoglobulins and had complete response of vasculitis. Several months later, two of these patients had relapse of MCV. Conclusions: B‐cell clones persist in MCV patients long after HCV infection has been cleared but halt the production of pathogenic antibody. These 'dormant' cells may be reactivated by events that perturb B‐cell homeostasis and can give rise to the relapse of cryoglobulinaemic vasculitis.